A genetic window to auditory-verbal problems in bipolar disorder. (December 2020) - Benítez-Burraco, Antonio
Abstract : Bipolar disorder is a high prevalent psychiatric condition entailing recurrent episodes of elevated mood and depression, but also diverse cognitive problems. One deficit observed in patients concerns to auditory-verbal processing. Being a hereditary condition with a complex genetic architecture, it is not clear which genes contribute to this deficit. We show that candidates for bipolar disorder significantly overlap with candidates for clinical conditions resulting from a deficit in the phonological loop of working memory, particularly, developmental dyslexia and specific language impairment. The overlapping genes are involved in aspects of brain development and function (particularly, brain oscillations) potentially underlying phonological processing and accordingly, emerge as promising candidates for auditory-verbal deficits in bipolar disorder. Abstract : Supplemental Digital Content is available in the text.